Idiombruk i talspråk - Arnstad, Maria (Nordiske Studier i Leksikografi, 2001)
This article is a study of the use of idioms in spoken Swedish. The study is based on a corpus, consisting of fifteen transcribed interviews with three native Swedish university students. The aim of the study is to explore the kinds of idioms used in the material, examine their forms, and compare them to their corresponding forms in a number of standard Swedish dictionaries. The comparison serves to observe the possible differences between the idiom constructions represented in the dictionaries and the forms actually used in speech. In addition to this, the idioms in the material are compared with the findings of another study, with the same purpose, but conceming the use of idioms in written text (Clausen, 1996). In this article, I put forward two interrelated hypotheses: I. The idioms used in written text are more varied than the idioms used in speech, in respect to the registered dictionary forms. 2. The idioms used in written text are of a different kind than the idioms used in speech. The first hypothesis is confirmed in my material, while the second is confirmed only to a certain extent.